2004
DOI: 10.1016/j.clpt.2004.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Carbamazepine regulates intestinal P-glycoprotein and multidrug resistance protein MRP2 and influences disposition of talinolol in humans

Abstract: Aside from induction of CYP3A4, carbamazepine acts as an inducer of intestinal MDR1 mRNA, MRP2 mRNA, and MRP2 protein content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
141
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(150 citation statements)
references
References 31 publications
6
141
0
3
Order By: Relevance
“…Induction of intestinal and/or hepatic MRP2 has been implicated to play a role in the interactions observed clinically between rifampin and morphine, mycophenolate mofetil, ezetimibe, and carvedilol (Fromm et al, 1997;Giessmann et al, 2004b;Oswald et al, 2006). Carbamazepine also increased talinolol elimination in humans, most likely by induction of P-gp and MRP2 (Giessmann et al, 2004a). Cho et al (2011) reported an induction of SLC22A1 mRNA encoding the uptake transporter OCT1 by rifampin in peripheral blood cells and enhanced glucose-lowering effects of metformin during rifampin administration.…”
Section: Induction Of Uptake and Efflux Transportersmentioning
confidence: 99%
“…Induction of intestinal and/or hepatic MRP2 has been implicated to play a role in the interactions observed clinically between rifampin and morphine, mycophenolate mofetil, ezetimibe, and carvedilol (Fromm et al, 1997;Giessmann et al, 2004b;Oswald et al, 2006). Carbamazepine also increased talinolol elimination in humans, most likely by induction of P-gp and MRP2 (Giessmann et al, 2004a). Cho et al (2011) reported an induction of SLC22A1 mRNA encoding the uptake transporter OCT1 by rifampin in peripheral blood cells and enhanced glucose-lowering effects of metformin during rifampin administration.…”
Section: Induction Of Uptake and Efflux Transportersmentioning
confidence: 99%
“…Finally, dysembryoplastic neuroepithelial tumors from patients undergoing AED treatment with various combinations of carbamazepine, oxcarbazepine, tiagabine, and lamotrigine, also exhibit increased MRP2 and MRP5 protein expression, compared with peritumoral tissue or samples obtained from patients diagnosed with arteriovenous malformations (Vogelgesang et al, 2004). Given that some AED medications are known to upregulate transporter expression in peripheral compartments [e.g., carbamazepine-induced induction of intestinal MRP2 mRNA and protein expression (Giessmann et al, 2004)], it is unclear whether the altered transporter expression observed in these various studies is due to the underlying disease, the therapies used to treat the disease, or a combination of the two.…”
Section: A Epilepsymentioning
confidence: 99%
“…It was also detected in renal brush-border membranes, the intestine (Schaub et al, 1997), placenta (St.-Pierre et al, 2000;Gerk and Vore, 2002), and brain (Török et al, 2003). In human carcinoma, MRP2 may confer resistance to chemotherapy (Norris et al, 1996;Nies et al, 2001;Young et al, 2001;Schinkel and Jonker, 2003), and it appears also to play a role in drug-drug interactions (Fromm et al, 2000;Bramow et al, 2001;Bode et al, 2002;Huisman et al, 2002;Giessmann et al, 2004).…”
mentioning
confidence: 99%